Bear feels ill - Wilson, Karma; Chapman, Jane, 1970- (London: : Simon and Schuster Books, 2007)
The forest friends all gather to help care for Bear when he feels sick, and when they come down with the same symptoms, the newly recovered Bear returns the favor.
2.1
K-3.
K-3
Keywords: Bears -- Juvenile fiction; Forest animals -- Juvenile fiction; Ilness -- Fiction; Bears -- Fiction; Forest animals -- Fiction; Ilness -- Fiction; Stories in rhyme; Bears -- Fiction; Forest animals -- Fiction; Ilness -- Fiction; Stories in rhyme